Recovery time profiling after short-, middle- and long-distance swimming performance - Piras, A.; Cortesi, M.; Campa, F.; Perazzolo, M.; Gatta, G. (The Journal of Strength and Conditioning Research, 2019)
We investigated cardiac autonomic responses and hemodynamic parameters on recovery time after short-, middle- and long-swimming performance. Ten male regional-level swimmers were tested to estimate time and frequency domains of arterial baroreflex sensitivity (BRS) and heart rate variability after 100, 200, and 400 m of front crawl. We found a BRS reduction for 90 minutes after a maximal 100- and 200-m front crawl event, meanwhile the reflex was restored back to the baseline value approximately 70 minutes after 400 m. The vagally mediated high-frequency power of R-R intervals was significantly reduced for 30 minutes after 400 m, and more than 90 minutes after 100 and 200 m, with a concomitant increase of sympathetic modulation. After 400 m, athletes have reduced their stroke volume for 50 minutes, which remained at the baseline level after 100 and 200 m. Heart rate was restored back after 90 minutes in all conditions, whereas total peripheral vascular resistance was significantly reduced for 50 minutes after 200 and 400 m, with a persistent reduction after 100 m. Time course of autonomic recovery after 3 different swimming performances is influenced by exercise intensity and duration, showing a rapid recovery after 400 m, an intermediate recovery after 200 m, and a significantly delayed recovery after a more strictly anaerobic performance like 100 m of front crawl. These results could encourage coaches to consider that athlete might be affected by the specific recovery time of the previous exercise performed, suggesting that the management of the exercise intensity, and appropriate monitoring of cardiac autonomic parameters might be helpful to know the physical condition of each athlete.